2020
DOI: 10.21037/jtd-20-1606
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional flow magnetic resonance imaging study to explain high prevalence of pulmonary vein stump thrombus after left upper lobectomy

Abstract: Background: Pulmonary vein (PV) stump thrombus, a known source of cerebral infarction, develops almost exclusively after left upper lobectomy; however, the mechanism remains unclear. We therefore evaluated the hemodynamics in the left atrium with four-dimensional flow magnetic resonance imaging (4D-flow MRI), which enables the simultaneous depiction of blood flow at three locations and the evaluation of hemodynamics. Methods: 4D-flow MRI was basically performed 7 days after lobectomy for cancer arising in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(40 reference statements)
2
12
1
Order By: Relevance
“…We previously showed that the SD of the flow rate, representing the grade of to-and-fro blood movement, was significantly correlated with the length of the PV stump (9). We also showed that both the SD and PV stump length were significantly greater in patients who underwent LUL than in those who underwent other lobectomies, which seemed to contribute to the high incidence of PV thrombus after LUL.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We previously showed that the SD of the flow rate, representing the grade of to-and-fro blood movement, was significantly correlated with the length of the PV stump (9). We also showed that both the SD and PV stump length were significantly greater in patients who underwent LUL than in those who underwent other lobectomies, which seemed to contribute to the high incidence of PV thrombus after LUL.…”
Section: Discussionmentioning
confidence: 87%
“…We previously evaluated regional hemodynamics by visualizing the blood streamlines in the left atrium from pulmonary veins as well as by the quantitative analysis of the blood flow around PV stump on four-dimensional flow magnetic resonance imaging (4D flow MRI) in patients who underwent lung lobectomy (9). We detected several characteristic blood flow patterns in the left atrium that were observed predominantly after LUL.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Another group evaluated the "turbulence" in the LA in patients after lobectomy. 60 Care should be taken that some of the methodologies for the evaluation have not been confirmed except for their own study without any reference to healthy participants. 61…”
Section: D Flow Mri Evaluation Of Post-lung Surgerymentioning
confidence: 99%
“…It is my great honor to express my opinion on the editorial commentary (1) regarding our paper, 'Four-dimensional flow magnetic resonance imaging study to explain high prevalence of pulmonary vein stump thrombus after left upper lobectomy' (2). Firstly, we observed dynamic blood movement in the left atrium after lung lobectomy with four-dimensional flow magnetic resonance imaging (4D MRI) and identified some characteristic hemodynamic features that are predominantly found after left upper lobectomy (LUL).…”
mentioning
confidence: 98%